Immunochemical characterization of high-molecular-weight polysaccharide from Fisher immunotype 3 Pseudomonas aeruginosa. - Pier, G B (1984)
A high-molecular-weight polysaccharide (PS) was isolated from the culture supernatant of a Fisher immunotype 3 (IT-3) strain of Pseudomonas aeruginosa. Consistent with previously reported findings for IT-1 and IT-2 PS, the preparation of IT-3 PS was found to be an immunogenic, nontoxic form of the O polysaccharide side chain on the lipopolysaccharide (LPS). The IT-3 PS was mainly carbohydrate in composition. It was serologically and chemically identical to LPS O side chain, but distinct from that structure in molecular size and immunogenicity. The IT-3 PS was nontoxic in mice and guinea pigs, nonpyrogenic in rabbits, and greater than 1,000-fold less reactive than IT-3 LPS in gelation of the Limulus amoebocyte lysate. Preliminary analyses by gas-liquid chromatography and 13C nuclear magnetic resonance have established the structural identity of IT-3 high-molecular-weight PS and the IT-3 O side chain. IT-3 PS was immunogenic in rabbits and mice. After active immunization, mice were protected against P. aeruginosa IT-3 intraperitoneal infection and burn wound sepsis. IT-3 PS also elicited protection against challenge with an IT-5 strain of P. aeruginosa, indicating that low-level contamination of the IT-3 PS with IT-3 LPS was not responsible for the immunogenic activity. These findings demonstrate the feasibility of preparing nontoxic immunogenic IT-3 PS capable of eliciting serotype-specific protective antibodies, employing methods similar to those previously described for the isolation of PS from other P. aeruginosa immunotypes.